Lignocellulose pretreatment technologies affect the level of enzymatic cellulose oxidation by LPMO. Issue 5 (12th May 2015) - Rodríguez-Zúñiga, Ursula Fabiola; Cannella, David; Giordano, Roberto de Campos; Giordano, Raquel de Lima Camargo; Jørgensen, Henning; Felby, Claus
<x xml:space="preserve">Abstract</x> Sugarcane bagasse, corn stover, and wheat straw are among the most available resources for the production of cellulosic ethanol.